HUBUNGAN KECERDASAN EMOSIONAL DENGAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA KELAS X SMKN 3 PONTIANAK - Hayuni, Nadila (Jurnal AlphaEuclidEdu, 2025)
This study aimed to examine the relationship between emotional intelligence and mathematical concept understanding among tenth-grade students at SMKN 3 Pontianak. Using a quantitative approach with correlational design, the research involved 36 students selected through simple random sampling. Data were collected using an emotional intelligence questionnaire consisting of 25 items and a mathematical concept understanding test with 7 items. The results showed that 22.22% of students had high emotional intelligence, 55.56% moderate, and 22.22% low. Similarly, for mathematical concept understanding, 25% of students were in the high category, 63.89% in moderate, and 11.11% in low category. Statistical analysis revealed a significant positive correlation between emotional intelligence and mathematical concept understanding (r = 0.780, p < 0.01). This indicates that students with higher emotional intelligence tend to demonstrate better understanding of mathematical concepts. The findings suggest the importance of considering emotional intelligence development in mathematics education to enhance students' conceptual understanding.